Microglial Inhibitory Mechanism of Coenzyme Q10 Against Aβ (1-42) Induced Cognitive Dysfunctions: Possible Behavioral, Biochemical, Cellular, and Histopathological Alterations - Singh, Arti; Kumar, Anil (Frontiers in Pharmacology, 2015)
Rationale: Alzheimer’s disease (AD) is a debilitating disease with complex pathophysiology. Amyloid beta (Aβ) (1-42) is a reliable model of AD that recapitulates many aspects of human AD. Objective: The present study has been designed to investigate the neuroprotective potential of Coenzyme Q10 (CoQ10) and its modulation with minocycline (microglial inhibitor) against Aβ (1-42) induced cognitive dysfunction in rats. Method: Intrahippocampal (i.h.) Aβ (1-42) (1µg/µl; 4µl/site) were administered followed by drug treatment with galantamine (2 mg/kg), CoQ10 (20 and 40 mg/kg), minocycline (50 and 100 mg/kg) and their combinations for a period of 21 days. Various neurobehavioral parameters followed by biochemical, acetylcholinesterase (AChE) level, proinflammatory markers (TNF-α), mitochondrial respiratory enzyme complexes (I-IV) and histopathological examinations were assessed. Results: Aβ (1-42) administration significantly impaired cognitive performance in Morris water maze (MWM) performance test, causes oxidative stress, raised AChE level, caused neuroinflammation, mitochondrial dysfunction and histopathological alterations as compared to sham treatment. Treatment with CoQ10 (20 and 40 mg/kg) and minocycline (50 and 100 mg/kg) alone for 21days significantly improved cognitive performance as evidenced by reduced transfer latency and increased time spent in target quadrant (TSTQ), reduced AChE activity, oxidative damage (reduced LPO, nitrite level and restored SOD, catalase and GHS levels), TNF-α level, restored mitochondrial respiratory enzyme complex (I, II, III, IV) activities and histopathological alterations as compared to control (Aβ (1-42) treated animals) group. Further, combination of minocycline (50 and 100 mg/kg) with CoQ10 (20 and 40 mg/kg) significantly modulate the protective effect of CoQ10 as compared to their effect alone. Conclusion: The present study suggests that the neuroprotective effect of CoQ10 could be due to its microglia inhibitory mechanism along with its mitochondrial restoring and anti-oxidant properties.